The Influence Of Using Telegram On The Writing Achievement Of XI Grade Students At Smkn 8 Surabaya - Nuzulul Rahma; Wahju Bandjarjani; Ferra Dian Andanty (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2018)
Writing is one of English skills that should be mastered by students. It is a skill that is more complicated than the others. Moreover, before writing students should master in vocabulay and grammar, because without them, they are not able to write. The present study aimed at finding out whether there is any influence or not telegram in teaching writing on students’ writing achievement at SMKN 8 Surabaya. This research used quantitative approach with true experimental design which consisted of two groups pre-test and post-test. The researcher gave pre-test to students before using telegram as a media and she gave post-test after using telegram for experimental class in XI Fashion Department 3 in SMKN 8 Surabaya. The t-test statistics was used to analyze the data. The result of the study showed that tcalculate was 2.0080 and ttable was 1.99773 with Df (Degree of freedom) 64 significant rate was 5% or 0.05, tcalculate was more than ttable. It meant that Ha was accepted and there was influence of telegram on students’ writing achievement. Based on the data anlysis, it could be concluded that telegram could be a suitable media in teaching-learning process, because it gave positive influence on writing.